Better than fiction - Martin, Alexa (Berkley Romance, 2022)
"Love isn't always by the books in this charming romantic comedy about a bookseller discovering how to be the main character in her story. As a self-proclaimed book hater and a firm believer that the movie is always better, Drew Young didn't anticipate inheriting her grandma's bookstore, The Book Nook. She's in way over her head even before the shop's resident book club, comprising six of the naughtiest old ladies ever, begins to do what it does best-meddle. Bestselling author Jasper Williams is a hopeless romantic. When he meets Drew at his Book Nook signing event, he becomes determined to show her the beauty of reading. He curates a book bucket list in exchange for her help exploring the local Denver scene for his current manuscript. From river rafting to local restaurants, Drew begins to connect with Jasper in a way she thought only happened in fiction. When messy family ties jeopardize the future of The Book Nook, Drew is caught between a bookshelf and a hard place. She's reminded that real life isn't always big dreams and sweeping romance. But Jasper is the plot twist she never saw coming, and he's writing a happily ever after just for them"--